Cardiovascular and Renal Outcomes With Canagliflozin According to Baseline Kidney Function: Data From the CANVAS Program. Issue 15 (9th October 2018) - Neuen, Brendon L.; Ohkuma, Toshiaki; Neal, Bruce; Matthews, David R.; de Zeeuw, Dick; Mahaffey, Kenneth W.; Fulcher, Greg; Desai, Mehul; Li, Qiang; Deng, Hsiaowei; Rosenthal, Norm; Jardine, Meg J.; et al.
Abstract : Background: Canagliflozin is approved for glucose lowering in type 2 diabetes and confers cardiovascular and renal benefits. We sought to assess whether it had benefits in people with chronic kidney disease, including those with an estimated glomerular filtration rate (eGFR) between 30 and 45 mL/min/1.73 m 2 in whom the drug is not currently approved for use. Methods: The CANVAS Program randomized 10 142 participants with type 2 diabetes and eGFR >30 mL/min/1.73 m 2 to canagliflozin or placebo. The primary outcome was a composite of cardiovascular death, nonfatal myocardial infarction, or nonfatal stroke, with other cardiovascular, renal, and safety outcomes. This secondary analysis describes outcomes in participants with and without chronic kidney disease, defined as eGFR <60 and ≥60 mL/min/1.73 m 2, and according to baseline kidney function (eGFR <45, 45 to <60, 60 to <90, and ≥90 mL/min/1.73 m 2 ). Results: At baseline, 2039 (20.1%) participants had an eGFR <60 mL/min/1.73 m 2, 71.6% of whom had a history of cardiovascular disease. The effect of canagliflozin on the primary outcome was similar in people with chronic kidney disease (hazard ratio, 0.70; 95% CI, 0.55–0.90) and those with preserved kidney function (hazard ratio, 0.92; 95% CI, 0.79–1.07; P heterogeneity = 0.08). Relative effects on most cardiovascular and renal outcomes were similar across eGFR subgroups, with possible heterogeneity suggested only for the outcome of fatal/nonfatal stroke ( P heterogeneity = 0.01), as were results for almost all safety outcomes. Conclusions: The effects of canagliflozin on cardiovascular and renal outcomes were not modified by baseline level of kidney function in people with type 2 diabetes and a history or high risk of cardiovascular disease down to eGFR levels of 30 mL/min/1.73 m 2 . Reassessing current limitations on the use of canagliflozin in chronic kidney disease may allow additional individuals to benefit from this therapy. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifiers: NCT01032629, NCT01989754. Abstract : Supplemental Digital Content is available in the text.